Efficacy and Safety of Ombitasvir/Paritaprevir/ Ritonavir + Dasabuvir ± Ribavirin Combinations in Patients with Genotype 1 Hepatitis C and Inherited Bleeding Disorders - Sonsuz, Abdullah; Bozcan, Selma; Hatemi, İbrahim; Özdemir, Sebati; Canbakan, Billur; Yıldırım, Süleyman; Gültürk, İlkay; Ar, Cem (Turkish Journal of Gastroenterology, 2022)
Background: Hepatitis C is one of the leading causes of death in patients with inherited bleeding disorders. Currently, direct-acting antiviral drugs used for the treatment of hepatitis C have become an effective and a reliable option for people with inherited bleeding disorders. The aim of this study is to report the efficacy and safety of ombitasvir + paritaprevir/ritonavir and dasabuvir combination in the treatment of hepatitis C in patients with inherited bleeding disorders. Methods: In this retrospective study, we evaluated the efficacy and safety of the combination of ombitasvir + paritaprevir/ritonavir and dasabuvir in 10 adult patients with hemophilia A, 4 patients with hemophilia B, and 1 patient with von Willebrand disease who were infected with hepatitis C genotype 1. Results: Five patients had genotype 1a and 10 patients had genotype 1b chronic hepatitis C. One patient had Child A cirrhosis, 14 patients had chronic hepatitis C without cirrhosis. Hepatitis C virus ribonucleic acid was negative in all patients at week 4 and at the end of the treatment. Sustained virologic response was obtained in all patients. Serious side effects were detected in 3 patients, which were intra- muscular bleeding, erosive gastritis-related gastrointestinal bleeding, and pneumonia. Conclusion: Ombitasvir + paritaprevir combined with ritonavir and dasabuvir ± ribavirin is an effective treatment for patients infected with genotype 1 hepatitis C who have coagulation disorders. Tolerance and side effects are similar to other treatment options. Cite this article as: Sonsuz A, Bozcan S, Hatemi İ, et al. Efficacy and safety of ombitasvir/paritaprevir/ritonavir + dasabuvir ± ribavirin combinations in patients with genotype 1 hepatitis C and inherited bleeding disorders. Turk J Gastroenterol. 2022;33(5):414-420.